Harmonia: a MuseScore's plugin to teach music - Araújo, João; Constante, Rogerio; Schiavoni, Flávio Luiz; Deluchi, Octávio (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
Information and Communication Technologies (ICTs) have been characterized as a very effective resource for promoting innovation in the way of teaching and learning. In relation to the musical area, computer software of musical notation, like MuseScore, has been more and more used for the musical compositions and to teach and learn music writing, musical arrangement, composition and counterpoint. MuseScore is a free software that can easily be applied to academic purposes, such as universities, for teaching students in music fields and can also be used in the professional life of students who have graduated from courses that use it. In addition, it allows the implementation of plugins for various purposes, such as the analysis of scores in relation to various preset parameters. In this context, this work aims to present the development of the Harmonia, an open source plugin for MuseScore focused on teaching musical analysis and automatic verification of scores based in harmony predefined rules.